MODEL PERANCANGAN MINI STUDIO FOTO SEBAGAI MEDIA PEMBUATAN PRODUK KERAJINAN POTRET POP ART - Johan Ies Wahyudi (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2019)
Applied research with the title "Design ofMini studio Model as media product making pop art portrait " is a study of the creation of the incoming skim applied. This study is based on the craft portrait silhouettes that already exist in society Surakarta. The downside of this craft is largely determined by the skill and sensitivity of the artist. The other drawback is the limited amount that can not be mass manufacture. Therefore it takes a miniature model photo studio that can help the process of making handicraft products portrait silhouette. In this study, the factors that will be developed are (1) the precision or accuracy of the silhouette of the model / figure to be made, (2) the development of the silhouette towards pop art more tasteful young people, and (3) reproductive techniques (digital printing) which allows for mass production and can be applied in various media such as paper, shirts, wood, metal or ceramic.